Phase‐Change Hyperbolic Heterostructures for Nanopolaritonics: A Case Study of hBN/VO2. Issue 18 (25th March 2019) - Dai, Siyuan; Zhang, Jiawei; Ma, Qiong; Kittiwatanakul, Salinporn; McLeod, Alex; Chen, Xinzhong; Corder, Stephanie Gilbert; Watanabe, Kenji; Taniguchi, Takashi; Lu, Jiwei; Dai, Qing; Jarillo‐Herrero, Pablo; et al.
Abstract: Unlike conventional plasmonic media, polaritonic van der Waals (vdW) materials hold promise for active control of light–matter interactions. The dispersion relations of elementary excitations such as phonons and plasmons can be tuned in layered vdW systems via stacking using functional substrates. In this work, infrared nanoimaging and nanospectroscopy of hyperbolic phonon polaritons are demonstrated in a novel vdW heterostructure combining hexagonal boron nitride (hBN) and vanadium dioxide (VO2 ). It is observed that the insulator‐to‐metal transition in VO2 has a profound impact on the polaritons in the proximal hBN layer. In effect, the real‐space propagation of hyperbolic polaritons and their spectroscopic resonances can be actively controlled by temperature. This tunability originates from the effective change in local dielectric properties of the VO2 sublayer in the course of the temperature‐tuned insulator‐to‐metal phase transition. The high susceptibility of polaritons to electronic phase transitions opens new possibilities for applications of vdW materials in combination with strongly correlated quantum materials. Abstract : In van der Waals heterostructures comprising hexagonal boron nitride (hBN) and vanadium dioxide (VO2 ), dynamic and reversible tuning of hyperbolic phonon polaritons is achieved via the insulator‐to‐metal phase transition by controlling the temperature. Using infrared nanospectroscopy, opposite tuning trends for in‐plane and out‐of‐plane phonon resonances are demonstrated during the phase transition.